Crystal structure of (2-((4-bromo-2,6-dichlorophenyl)amino)phenyl) (morpholino)methanone, C17H15BrCl2N2O2 - Zhang Cuiya; Han Xiaojuan; Tang Wenqiang (Zeitschrift für Kristallographie - New Crystal Structures)
C17H15BrCl2N2O2, monoclinic, P21/c (no. 14), a = 20.333(7) Å, b = 11.226(5) Å, c = 7.843(3) Å, β = 99.651(8)°, V = 1764.8(12) Å3, Z = 4, Rgt(F) = 0.0464, wRref(F2) = 0.1601, T = 173 K.